Privatization Policy with Corporate Social Responsibility in a Mixed Duopoly - Liang, He; Sun, Chaoqun; Gao , Jiaqi (Transformations In Business & Economics, 2025)
This paper constructs a mixed duopoly model considering privatization, the level of corporate social responsibility (CSR), and the cost of state-owned shares. It examines the equilibrium results under the Cournot model and the Stackelberg model and makes comparisons. The results show that CSR and state-owned shares have essential effects on equilibrium results. Faced with different types of competition, stakeholders make various decisions. Under the Cournot model, there is an optimal state-owned share proportion. Full privatization is optimal under the Stackelberg model and the expanded three-stage game. Therefore, state-owned shares, CSR, and competition mode should be considered in the privatization policy.